2014
DOI: 10.1120/jacmp.v15i4.4658
|View full text |Cite
|
Sign up to set email alerts
|

A dosimetry technique for measuring kilovoltage cone‐beam CT dose on a linear accelerator using radiotherapy equipment

Abstract: This work develops a technique for kilovoltage cone‐beam CT (CBCT) dosimetry that incorporates both point dose and integral dose in the form of dose length product, and uses readily available radiotherapy equipment. The dose from imaging protocols for a range of imaging parameters and treatment sites was evaluated. Conventional CT dosimetry using 100 mm long pencil chambers has been shown to be inadequate for the large fields in CBCT and has been replaced in this work by a combination of point dose and integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…It is recommended that users measure the dose for at least the minimum and maximum dose CBCT protocols for a centrally located ion chamber annually to determine if the range of CBCT doses has remained constant. Once the baseline dose has been measured, an additional method for kV‐CBCT dose constancy would be to use an ionization chamber in air 136,137 …”
Section: Qa Of Medical Acceleratorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is recommended that users measure the dose for at least the minimum and maximum dose CBCT protocols for a centrally located ion chamber annually to determine if the range of CBCT doses has remained constant. Once the baseline dose has been measured, an additional method for kV‐CBCT dose constancy would be to use an ionization chamber in air 136,137 …”
Section: Qa Of Medical Acceleratorsmentioning
confidence: 99%
“…Once the baseline dose has been measured, an additional method for kV-CBCT dose constancy would be to use an ionization chamber in air. 136,137 The times for each task are estimated based on the assumption that each task is carried out independently. As tools are commercially available to address multiple tasks with a single image acquisition, the overall time required to accomplish several tasks in the same category, such as planar kV imaging, can substantially speed up the QA process.…”
Section: Review Of the Problemmentioning
confidence: 99%
“…Currently, imaging dose is often omitted from treatment plans since, being typically less than 1 Gy for an entire treatment schedule or 1–10 cGy for a single scan, it is two orders of magnitude smaller than the therapeutic doses . However, during an imaging procedure, large portions of the body are irradiated, including radiosensitive structures such as lung, breast, thyroid, and reproductive organs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of kV-CBCT imaging often results in additional patient radiation exposure to radiosensitive organs. Scandurra et al 2 reported that an absolute dose of the head protocol was 0.9 cGy, while previous research indicated that image-guided kV-CBCT was effective for the evaluation of set-up accuracy. [3][4][5][6] Delishaj et al 7 suggested that kV-CBCT should first be administered as three fractions and then followed by weekly doses to significantly reduce set-up errors in head and neck cancer treatment using the IMRT technique.…”
mentioning
confidence: 99%